2004
DOI: 10.1080/00224490409552223
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity, sexual behaviors, and sexual attitudes during emerging adulthood

Abstract: The current study examined associations between religiosity and sexual behaviors and attitudes during emerging adulthood. Two hundred and five emerging adults completed surveys about five aspects of their religiosity (group affiliation, attendance at religious services, attitudes, perceptions of negative sanctions, and adherence to sanctions) and their sexual behaviors (abstinence, age of onset, lifetime partners, condom use) and attitudes (conservative attitudes, perceived vulnerability to HIV, and condom-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
175
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(200 citation statements)
references
References 30 publications
18
175
2
3
Order By: Relevance
“…Unlike other studies (e.g., Lefkowitz et al, 2004;Miller & Gur, 2002;Rostosky et al, 2003), this study did not assess the subjective importance of religion or individuals' beliefs about the importance of religion in shaping their sexual behavior and attitudes. However, different measures of religiosity are often highly correlated (e.g., those who attend services more frequently also give a greater importance to their religious beliefs) such that the different measures are often combined to form a composite index of religiosity (e.g., Hardy & Raffaelli, 2003;Meier, 2003;Pluhar, Frongillo, Stycos, & Dempster-McClain, 1998).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Unlike other studies (e.g., Lefkowitz et al, 2004;Miller & Gur, 2002;Rostosky et al, 2003), this study did not assess the subjective importance of religion or individuals' beliefs about the importance of religion in shaping their sexual behavior and attitudes. However, different measures of religiosity are often highly correlated (e.g., those who attend services more frequently also give a greater importance to their religious beliefs) such that the different measures are often combined to form a composite index of religiosity (e.g., Hardy & Raffaelli, 2003;Meier, 2003;Pluhar, Frongillo, Stycos, & Dempster-McClain, 1998).…”
Section: Discussionmentioning
confidence: 80%
“…The most comprehensive operationalization of religion/religiosity is that of Lefkowitz et al (2004), who assessed identity (affiliation), behavior (frequency of attendance), attitude (subjective importance of religion), perception (the religion's views of sex), and practice (adherence to the religion's views of sexual behavior). However, as suggested above, only in studies designed specifically for the analyses of religion/religiosity could sufficient space be devoted to a comprehensive operationalization of these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research supported that adolescents who were more religious tended to delay sexual activity (Kirby 2002;Rostosky et al 2004). For male and female teens, frequent attendance at religious services and religious youth activities, higher levels of importance of religion in daily life and religious feelings, and increased adherence to religious teachings were all significantly related to decreased rates of voluntary sexual debut (Fehring et al 1998;Holder et al 2000;Lammers et al 2000;Lefkowitz et al 2004;McCree et al 2003;Nonnemaker et al 2003;Rostosky et al 2003). Having increased levels of social support from friends in a faith context was related to decreased likelihood of sexual initiation as was having peers who attended church regularly (Holder et al 2000;Manlove et al 2008;Mott et al 1996).…”
Section: Religiositymentioning
confidence: 99%
“…DuRant and Sanders (1989) found sexually active adolescent girls who frequently attended worship services reported a lower frequency of participation in sexual intercourse than those who attended worship services less frequently. Lefkowitz et al (2004) found sexually active Catholics reported fewer lifetime sexual partners than sexually active Protestants.…”
mentioning
confidence: 99%